PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN HUTANG DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2020 - pulungan wati Mega; Rokhmawati Andewi; Fitri Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to examine the effect of dividend policy, debt policy, andprofitability on firm value. This research was conducted on various industrialsector manufacturing companies listed on the Indonesia Stock Exchange by takingdata through the official website of the Indonesia Stock Exchange (IDX)www.idx.co.id and www.finance.yahoo.com. This research was conducted in theperiod 2016-2020. The population in this study amounted to 51 companies, whilethe sample in this study amounted to 40 companies using purposive samplingmethod. Data analysis used multiple linear regression. The results of this studyindicate that: dividend policy has a significant positive effect on firm value, debtpolicy has a significant positive effect on firm value, profitability has a significantpositive effect on firm value. Keywords: Dividend Policy, Debt Policy, Profitability and Firm Value